2016
DOI: 10.1161/circep.115.003723
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in the Clinical and Pathological Characteristics of Victims of Sudden Cardiac Death in the Absence of Previously Identified Heart Disease

Abstract: Because the primary prevention strategies, public awareness of early symptoms of CAD, and secondary prophylaxis has changed during the past 2 decades, we studied the temporal trends in the pathogenesis of unexpected SCD during

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…ST2 acts as a decoy receptor for IL-33, thus blocking its protective effects. It has been reported that mice treated with soluble ST2 developed signi cantly larger atherosclerotic plaques in the aortic sinus of the ApoE(-/-) mice compared with the control mice [23].These results suggested that ST2 may be proposed as a marker of plaque burden and predictors of future cardiovascular event [24].Although the above data suggest that ST2 has a role in the prognosis of patients presenting with an acute coronary syndrome, whether ST2 contributes to cardiovascular risk prediction in a large scale CAD patients during a long-term follow up remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…ST2 acts as a decoy receptor for IL-33, thus blocking its protective effects. It has been reported that mice treated with soluble ST2 developed signi cantly larger atherosclerotic plaques in the aortic sinus of the ApoE(-/-) mice compared with the control mice [23].These results suggested that ST2 may be proposed as a marker of plaque burden and predictors of future cardiovascular event [24].Although the above data suggest that ST2 has a role in the prognosis of patients presenting with an acute coronary syndrome, whether ST2 contributes to cardiovascular risk prediction in a large scale CAD patients during a long-term follow up remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…However, the rate of SCD in the nonischemic cardiomyopathy population remains unacceptably high. Up to 35% of deaths in these patients are sudden, with an annual SCD incidence of 2% to 3%, often occurring in previously asymptomatic patients 21,22 . Because patients with NICM are typically younger and have less comorbid illness compared with patients with ischemic cardiomyopathy, they may be expected to derive substantial benefit from ICD therapy via avoidance of SCD 1 .…”
Section: Discussionmentioning
confidence: 99%
“…ST2 acts as a decoy receptor for IL-33, thus blocking its protective effects. It has been reported that mice treated with soluble ST2 developed signi cantly larger atherosclerotic plaques in the aortic sinus of the ApoE (-/-) mice compared with the control mice [32]. Researchers have found that ST2 are particularly expressed in arterial endothelial cells, involving in the progression of atherosclerosis [33].…”
Section: The Underlying Mechanismsmentioning
confidence: 99%